The clansman : an historical romance of the Ku Klux Klan - Dixon, Thomas, Jr., 1864-1946 (Routledge, 2015)
Thomas Dixon was a lawyer, North Carolina state legislator, Baptist minister, lecturer, and novelist. This novel, an abridgement by Cary Wintz was originally published in 1905. It reflects turn-of-the-century attitudes most southerners had about Republican rule during Reconstruction.